Detroit to Fort Sackville, 1778-1779 The Journal of Normand MacLeod - MacLeod, Normand (Wayne State University Press, 2017)
In 1777 Normand MacLeod, a British army officer, assumed the post of town major of Detroit, then a British colony on the frontier of late eighteenth-century America. Although it was not in the forefront of action in the American Revolution, the fort at Detroit had an important role because its strategic location made it a point of interest to military leaders on both sides. Under the leadership of Captain Normand MacLeod, the city of Detroit played a role in the War for Independence that is described in detail in this journal. During the bitter winter of 1778-79, MacLeod led a party of Detroit Volunteer Militia in advance of Henry Hamilton's main force. Hamilton was attempting to hold Fort Sackville (modern Vincennes, Indiana) against George Rogers Clark and his troops. MacLeod was a shrewd and witty reporter. His diary, published for the first time in this volume, details the daily routine of the arduous midwinter military campaign. He describes daily life within the walls of the fort at Detroit, the military adventures planned within those walls, and the rumors, the gossip, and the personal relationships within the community.Offering an unprecedented personal glimpse of Detroit life in the years 1778-79, the diary preserves the flavor of one bitter winter of the American Revolution of special significance for historians of Michigan and Detroit. William A. Evans's introduction to the journal places MacLeod's expedition in the context of Hamilton's strategy and provides a biographical account of MacLeod himself that has not been available previously.